2004
DOI: 10.1089/153056204773644535
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Cognitive-Behavior Therapy for Panic Disorder with Agoraphobia in Videoconference

Abstract: Delivering psychotherapy by videoconference could significantly increase the accessibility of empirically validated treatments. The aim of this study was to compare the effectiveness of cognitive-behavior therapy (CBT) for panic disorder with agoraphobia (PDA) when the therapy is delivered either face-to-face or by videoconference. A sample of 21 participants was treated either face-to-face or by videoconference. Results showed that CBT delivered by videoconference was as effective as CBT delivered face-to-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
179
0
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(210 citation statements)
references
References 46 publications
13
179
0
18
Order By: Relevance
“…55 A small study gave a preliminary indication that video conferencing is an acceptable method of delivery for CBT for people who have panic disorder with agoraphobia. 56 Schizophrenia. An RCT of an Internet-based approach found that the intervention group reported lower perceived stress than the usual care group.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%
“…55 A small study gave a preliminary indication that video conferencing is an acceptable method of delivery for CBT for people who have panic disorder with agoraphobia. 56 Schizophrenia. An RCT of an Internet-based approach found that the intervention group reported lower perceived stress than the usual care group.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%
“…A maioria (n = 5) dos estudos realizou psicoterapia individual (Bouchard et al, 2004;Ertelt et al, 2011;Germain, Marchand, Bouchard, Guay, & Drouin, 2010;Stubbings, Rees, Roberts, & Kane, 2013;Vogel et al, 2012), mas dois artigos realizaram intervenção em grupo (Greene et al, 2010;Morland et al, 2014) e dois conduziram terapia de família (Carey, Wade, & Wolfe, 2008;Freeman, Duke, & Harris, 2013).…”
Section: Características E Métodos Dos Estudosunclassified
“…Seis estudos aplicaram o Working Alliance Inventory (WAI) (Bouchard et al, 2004;Ertelt et al, 2011;Freeman et al, 2013;Germain et al, 2010;Stubbings et al, 2013;Vogel et al, 2012), sendo que dois deles utilizaram a versão reduzida do instrumento (Stubbings et al, 2013;Vogel et al, 2012). Dois artigos utilizaram a versão abreviada da Group Therapy Alliance Scale (GTAS) (Greene et al, 2010;Morland et al, 2014) e um estudo utilizou a Agnew Relationship Measure (ARM) (Carey et al, 2008).…”
Section: Avaliação Da Aliança Terapêutica Nas Tccs Por Videoconferênciaunclassified
See 1 more Smart Citation
“…Partindo desse argumento, Prado e Meyer (2006) enfatizam a necessidade de pesquisar a possibilidade da relação terapêutica nas terapias virtuais, sendo esse um primeiro passo para avaliar a terapia via internet e avançar no desenvolvimento dos serviços mediados por computador. Alguns países, como Canadá e Holanda, entre outros, já realizaram pesquisas empíricas e metanálises mostrando resultados positivos dos atendimentos on-line para diversos tipos de transtornos psiquiátricos, como ansiedade, depressão e fobias (van Bastelaar, Cuijpers, Pouwer, Riper & Snoek, 2011;Bouchard et al, 2004;Spek et al, 2007).…”
Section: Introductionunclassified